Outcomes Assessment in International Education - Deardorff, Darla K (International Higher Education, 2014)
There is an increased focus in recent years on outcomes assessment in international education. What makes for good assessment? This article explores some key principles and guiding questions to explore as higher education institutions strengthen their efforts in assessment.